Reading the Visual:: Representation and Narrative in the Construction of Heritage - Watson, Steve; Waterton, Emma (Material Culture Review)

(untitled) (National Museums of Canada, 2010)
Abstract This paper examines the power of "the visual" in representations of culture and heritage tourism. While the visual is fundamental to the ways material culture is represented, the focus on objects and artifacts has obscured the very processes that animate and privilege them in the production of heritage. As a result, material culture is classified and categorized, placed in temporal sequences and variously interpreted without much thought as to its social and cultural contexts. In this paper, we seek to relocate "heritage" in relation to aesthetics and the inherent value of the object. We examine visuality as a key part of the process by which cultural heritage is produced and which, in turn, enables visual culture to be "read" as a narrative of identity, politics and power.